Daratumumab, pomalidomide, and dexamethasone as a bridging therapy to autologous stem cell transplantation in a case of systemic light-chain amyloidosis with advanced cardiac involvement. (June 2019) - Arnall, Justin R; Usmani, Saad Z; Adamu, Hawawu; Mishkin, Joseph; Bhutani, Manisha
Systemic light-chain (AL) amyloidosis is a rare hematologic disorder where proteins infiltrate tissues leading to organ failure and death. Cardiac involvement, present in ∼70% of patients, determines stage and prognosis of the disease, with advanced involvement having a median survival of six months. The treatment of light-chain amyloidosis is directed at recovering organ function with therapeutic strategies following those of multiple myeloma with plasma cell-directed therapies. The use of single agent daratumumab has been reported in light-chain amyloidosis achieving rapid and deep responses. The combination of daratumumab, pomalidomide, and dexamethasone (DaraPomD) is particularly interesting for severe AL based on success in multiple myeloma. A 43-year-old female with light-chain amyloidosis and concomitant multiple myeloma presented with severe bowel dysmotility causing abdominal pain, anemia, and a 100-pound unintentional weight loss. A combination of cyclophosphamide, bortezomib, and dexamethasone was initiated but after five cycles her symptoms were progressing and therapy was switched to DaraPomD to optimize response. At the conclusion of two cycles she had achieved an amyloid complete-hematologic response, with her recurring ileus and abdominal pain significantly improved. Additionally, cardiac markers also suggested a rapid response without a common paradoxical worsening of congestive heart failure, and was overall well tolerated. Given the severe symptoms and refractory nature of our patient's disease DaraPomD was reasonable. With the tolerability and response seen, this patient experience supports a formal clinical trial evaluating the safety and efficacy of DaraPomD in light-chain amyloidosis.